‘Autistic’ Traits in Non-Autistic Japanese Populations: Relationships with Personality Traits and Cognitive Ability - Kunihira, Yura; Senju, Atsushi; Dairoku, Hitoshi; Wakabayashi, Akio; Hasegawa, Toshikazu (Journal of autism and developmental disorders, 2006)
We explored the relationships between "autistic" traits as measured by the AQ (Autism-Spectrum Quotient; Baron-Cohen et al., J. Autism Develop. Disord. (2001b) 31 5) and various personality traits or cognitive ability, which usually coincide with autistic symptoms, for general populations. Results showed the AQ was associated with tendencies toward an obsessional personality as defined by the TCI (Temperament and Character Inventory), higher depression and anxiety, and higher frequency of experience of being bullied. These results parallel the patterns in autism and corroborate the validity of the AQ for general populations. Contrary to our prediction, however, there was no relationship between the AQ and cognitive ability, such as theory of mind, executive functioning, and central coherence, suggesting the AQ does not reflect autism-specific cognitive patterns in general populations.